NADH-based kinetic model for acetone-butanol-ethanol production by Clostridium - Quintero-Díaz, Juan Carlos; Mendoza, Diego F.; Avignone-Rossa, Claudio (Frontiers in Bioengineering and Biotechnology, 2023)
We present in this work a kinetic model of the acetone-butanol-ethanol (ABE) fermentation based on enzyme kinetics expressions. The model includes the effect of the co-substrate NADH as a modulating factor of cellular metabolism. The simulations obtained with the model showed an adequate fit to the experimental data reported by several authors, matching or improving the results observed with previous models. In addition, this model does not require artificial mathematical strategies such as on-off functions to achieve a satisfactory fit of the ABE fermentation dynamics. The parametric sensitivity allowed to identify the direct glucose → acetyl-CoA → butyryl-CoA pathway as being more significant for butanol production than the acid re-assimilation pathway. Likewise, model simulations showed that the increase in NADH, due to glucose concentration, favors butanol production and selectivity, finding a maximum selectivity of 3.6, at NADH concentrations above 55 mM and glucose concentration of 126 mM.The introduction of NADH in the model would allow its use for the analysis of electrofermentation processes with Clostridium, since the model establishes a basis for representing changes in the intracellular redox potential from extracellular variables.